IMPLEMENTASI MODEL PEMBELAJARAN SOSIAL EMOSIONAL SEL PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV - Fidini Ilmi, Cindy; Linda Zakiah; Juhana Sakmal (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to theoretically implement the Social Emotional Learning (SEL) learning model in the fourth grade of Indonesian language classes in Elementary Schools. Using a qualitative approach based on literature studies, this study presents many academic findings and research findings that are up-to-date and relevant, both domestically and internationally. The research findings indicate that the use of the SEL model in Indonesian language teaching has a positive impact on students' development of five core competencies—self-awareness, self-reliance, social skills, relating, and a strong sense of self-esteem. The SEL model helps students express their emotions, understand others' perspectives, and improve their communication skills, both in writing and orally. In addition, the integration of SEL in Indonesian language teaching also promotes an inclusive, reflective, and supportive learning environment for students. This study recommends the need for the development of Indonesian language learning strategies based on SEL systematically and contextually to support holistic student growth.